2020
DOI: 10.5617/njhe.7070
|View full text |Cite
|
Sign up to set email alerts
|

Health care and long-term care costs by age and proximity to death in a publicly funded universal system: A descriptive study of population data

Abstract: Trends in population ageing parallel concerns with escalating health care expenditures. The purposes of this study are to (1) estimate the distribution of health care and long-term care costs to ascertain the relative importance of age vs. proximity to death as the main driver of costs; (2) explore the relative importance of user rates and costs per user as the primary driver of per capita costs of selected services for survivors and decedents, respectively; and (3) provide projections of future costs. We use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Older men and women are known to utilise healthcare differently due to variation in lifespan and diagnoses 31. For example, a 2020 Norwegian study on healthcare utilisation trends observed that men were admitted to hospitals more frequently, whereas women had higher use of home-based healthcare services and more general practitioner consultations 27. Reports from the Norwegian Institute of Public Health show that cardiovascular and respiratory diagnoses are overall more prevalent in Norwegian men than women 32 33.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Older men and women are known to utilise healthcare differently due to variation in lifespan and diagnoses 31. For example, a 2020 Norwegian study on healthcare utilisation trends observed that men were admitted to hospitals more frequently, whereas women had higher use of home-based healthcare services and more general practitioner consultations 27. Reports from the Norwegian Institute of Public Health show that cardiovascular and respiratory diagnoses are overall more prevalent in Norwegian men than women 32 33.…”
Section: Discussionmentioning
confidence: 99%
“… 31 For example, a 2020 Norwegian study on healthcare utilisation trends observed that men were admitted to hospitals more frequently, whereas women had higher use of home-based healthcare services and more general practitioner consultations. 27 Reports from the Norwegian Institute of Public Health show that cardiovascular and respiratory diagnoses are overall more prevalent in Norwegian men than women. 32 33 Previous studies suggest that these conditions are associated with both higher mortalities, multimorbidity and high costs, 34 35 as indicated by the high number of participants who died in the high-cost group in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Deceased group had higher total costs compared to other groups of pathways, mainly resulting from large volume of specialized inpatient care. This is not surprising, since healthcare costs have been shown to increase notably in close proximity to death [ 27 ].…”
Section: Discussionmentioning
confidence: 99%